Counteracting foaming caused by lipids or proteins in biogas reactors using rapeseed oil or oleic acid as antifoaming agents. (1st August 2015) - Kougias, P.G.; Boe, K.; Einarsdottir, E.S.; Angelidaki, I.
Abstract: Foaming is one of the major operational problems in biogas plants, and dealing with foaming incidents is still based on empirical practices. Various types of antifoams are used arbitrarily to combat foaming in biogas plants, but without any scientific support this action can lead to serious deterioration of the methanogenic process. Many commercial antifoams are derivatives of fatty acids or oils. However, it is well known that lipids can induce foaming in manure based biogas plants. This study aimed to elucidate the effect of rapeseed oil and oleic acid on foam reduction and process performance in biogas reactors fed with protein or lipid rich substrates. The results showed that both antifoams efficiently suppressed foaming. Moreover rapeseed oil resulted in stimulation of the biogas production. Finally, it was reckoned that the chemical structure of lipids, and more specifically their carboxylic ends, is responsible for their foam promoting or foam counteracting behaviour. Thus, it was concluded that the fatty acids and oils could suppress foaming, while salt of fatty acids could generate foam. Highlights: Rapeseed oil and oleic efficiently counteracted foam caused by proteins or lipids. Rapeseed oil was more suitable antifoam stimulating the methane production. Foam or antifoam behaviour of lipids is correlated with their chemical structure. Fatty acids and oils suppress foam while salt of fatty acids promote foam.